A Vietnamese adaptation of the attitudes and beliefs regarding aggression questionnaire. Issue 2 (3rd April 2023) - Vu, Ba Tuan; Van Heel, Martijn; Bosmans, Guy
ABSTRACT: There has been an increase in peer violence in Vietnam. Although normative beliefs approving aggression have been considered an important factor in the development of peer violence in Western countries, few studies examine the factor in Vietnamese context. This limitation may be due to the lack of a validated scale used to evaluate the factor. The current study aims to translate and validate the Vietnamese version of the Attitudes and Beliefs Regarding Aggression (ABRA). We used two independent samples of Vietnamese adolescents. The first sample included 411 participants (47.2% boys, aged 11–16, M age  = 14.00, SD  = 1.12), whereas the second sample included 310 adolescents (51.6% boys, age 10–15, M age  = 12.67, SD = 1.61). Results obtained from confirmatory factor analyses and item response theory analyses suggested the use of two out of three subscales of the ABRA: the Aggression Legitimate and the Aggression Pays subscales. Additionally, the two subscales were indicated to be reliable in terms of both internal consistency and test-retest. Finally, results obtained from multiple hierarchical analyses suggested the criterion validity of the two subscales. In sum, the Vietnamese ABRA is a valid measure of normative beliefs approving aggression in Vietnamese adolescents.